Optimalisasi keterlibatan orang tua dalam implementasi Kurikulum Merdeka pada pendidikan anak usia dini di pedesaan - Silmi Indah Fakhira; Zainal Arifin; Mario Emilzoli (Universitas Pendidikan Indonesia, 2026)
This study was motivated by the limited parental involvement in supporting the implementation of the Kurikulum Merdeka in Early Childhood Education, particularly in rural areas, where the curriculum emphasizes collaboration between schools and families for children's holistic development. This study aims to analyze strategies for optimizing parental involvement in supporting the implementation of the Kurikulum Merdeka in rural Early Childhood Education. It employed a literature review method, collecting data from journal articles, reports, and other relevant documents. The findings indicate that parental involvement in rural areas continues to face challenges, including limited understanding of early childhood education and the Kurikulum Merdeka, the perception that education is solely the school's responsibility, and time constraints resulting from work and economic conditions. To address these challenges, strategies such as establishing communication early, strengthening open and continuous communication, utilizing accessible digital media, implementing ongoing parenting programs, and involving parents in school activities can strengthen collaboration between schools and families in rural Early Childhood Education settings.